Career patterns of academic librarians - Madalogdog, Ralisa M. (2002)
The purpose of this study was to examine the present trends in the careers of academic librarians in Metro Manila. Relationships between variables were also determined. This study determined the predominant personal characteristics of academic librarians in Metro Manila, the prevailing professional qualifications of these academic librarians, and their job satisfaction.